An Approach to the Green Area Parameter in Urban Transformation - Polat, Halil Ibrahim (Salehan Institute of Higher Education, 2017)
In this study, the green area value is obtained from the feasibility reports which are made in 4, 6-hectare region that is declared as a risky area within the framework of the Law of Transformation of Areas Under Disaster Risk (No. 6306) and Implementation Regulation and the green area per capita (m2/person) is determined. In urban planning in which all of the land-use, social, technical infrastructure parameters need to be considered at the optimum level as a whole, according to this article; even if only the green area data is taken into consideration, the importance of making a transformation decision for the region is supported by the analysis. In this context; an analysis and calculation model has been proposed with the parameters defined in suggestion form which is bordered with the boundary value conditions in the light of international and national data. In the current situation, development plansâ situation and the draft case, it is tried to compare the amounts of the green areas and to give an approach for the green area ratio per capita.